Application of a Novel AAV Gene Therapy: Investigating AAV6.2-FF in Models of Pulmonary Surfactant-Related Disease - Nangle, Kennedy (Université d'Ottawa | University of Ottawa, 2024)
Surfactant proteins are a group of proteins responsible for maintaining a healthy lung by lowering surface tension in the alveoli and facilitating proper homeostasis of pulmonary surfactant components at the air-liquid interface. Surfactant protein B and C have been associated with disease as a result of genetic mutations disrupting the function of these critical proteins. Mutations in the Surfactant protein C gene (SFTPC) are known to cause Pulmonary Fibrosis (PF), a rare, chronic, lethal lung condition characterized by the build up of scar tissue in the pulmonary space. Mutations in the SFTPB gene are associated with a rare, lethal condition, SP-B deficiency. This condition presents neonatally and is characterized by respiratory distress and neonatal death within the first weeks of life. There are currently no treatments for either condition and lung transplantation is the only opportunity for a cure. The clear genetic etiology of both conditions offers the possibility of treatment through gene therapy. Recently, our lab has shown the potential of a novel viral vector gene therapy (AAV6.2-FF) for the treatment of SP-B deficiency, restoring expression of the Sftpb gene and extending the lifespan of SP-B deficient mice by over 300+ days compared to controls. Additionally, our lab has extended the use of this gene therapy platform for the treatment for Sftpc-related pulmonary fibrosis in a transgenic mouse model of the most common mutation (I73T) associated with the disease (manuscript in review). This thesis focuses on a potential therapy transfer of the Sftpc gene therapy to another common SFTPC mutation, L184Q. This thesis also addresses the characterization of re-administration of the AAV6.2-FF vector in Sftpb mice in order to expand on the potential clinical translation of the therapy. Both models were established and feasibility of the therapeutic expansion of these models was assessed. In the model of Sftpc-L184Q knock- in, the administration of bleomycin resulted in a significant increase in fibrosis, as measured by the Ashcroft-Hubner score, a significant change in lung structure, by proxy of the Mean Linear Intercept, and a significant decrease in lung function. Taken together, this demonstrates the successful development of injury in this mouse model. The administration of the AAV6.2-FF gene therapy resulted in a significant expression of the Sftpc transgene in the lung tissue of the L184Q mice, demonstrating the potential of the therapeutic in the L184Q model. Further studies assessing the combination of the injury model and administration of the therapeutic are required. A difference in phenotype between LQ and I73T mice was explored and investigations into this phenotype have laid the foundation for future exploration.
Keywords: Gene Therapy; Surfactant Disorders; AAV; Pulmonary Fibrosis